2022
DOI: 10.15740/has/ijps/17/ocaebgd/1-11
|View full text |Cite
|
Sign up to set email alerts
|

Study on economics of biochar application in cotton – maize – cowpea cropping sequence under integrated nutrient management

Abstract: The highest net return was found in continuous application (two times) especially in the treatment biochar @ 10 t + 100 % NPK + FYM with Rs.67,928 ha-1 followed by biochar @ 10 t + 75 % NPK + FYM treatment with Rs.67,172 ha-1. The next higher net return was registered in biochar @ 10 t + 75 % NPK + FYM treatment under one time application with Rs. 62,970/-.Comparing the studies, the two times application (biochar @ 10 t ha-1 time-1) recorded an addition of Rs. 5,565/- only over one time application. Therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Reports say that the biochar yield is highly dependant on the pyrolysis conditions such as temperature, heating rate and residence time (Uzun et al, 2006;Tsai et al, 2007) [29,28] and is also greatly influenced by physical, chemical and biological properties of the raw materials used ( . Elangovan (2014) [8] reported recovery percentage of 12 to 40, when pyrolysis was done using different biological residues. Phuong et al (2015) [21] concluded that the decrease in biochar yield might be due to the thermal decomposition of organic material present in the residues.…”
Section: Resultsmentioning
confidence: 99%
“…Reports say that the biochar yield is highly dependant on the pyrolysis conditions such as temperature, heating rate and residence time (Uzun et al, 2006;Tsai et al, 2007) [29,28] and is also greatly influenced by physical, chemical and biological properties of the raw materials used ( . Elangovan (2014) [8] reported recovery percentage of 12 to 40, when pyrolysis was done using different biological residues. Phuong et al (2015) [21] concluded that the decrease in biochar yield might be due to the thermal decomposition of organic material present in the residues.…”
Section: Resultsmentioning
confidence: 99%